Frequency and Treatment Outcome of Invasive Fungal Infections in Children with Hematological Malignancies - Rabiha Manzoor; Rabia Tariq; Awais Arshed; Qurat Ul Ain Ali; Ajaz Ahmed; Fozia Sayed Rasool (Pakistan Journal of Medicine and Dentistry)
Background: Invasive fungal infections are the cause of significant morbidity and mortality among cancer patients of any age group. This research aimed to determine the frequency and treatment outcome of invasive fungal infections in children with hematological malignancies.